London Metal Exchange: Causality Relationship between the Price Series of Non-Ferrous Metal Contracts - Basoglu, Mustafa Serdar; Korkmaz, Turhan; Cevik, Emrah Ismail (International Journal of Economics and Financial Issues, 2014)
Fluctuations in raw material and product prices have caused manufacturers and consumers to experience serious losses in steel sector as well as in all other sectors. As the number of manufacturers of commodities like coking coal, iron ore and scrap- the main raw materials of steel manufacturing- is less worldwide and their manufacturers do not want to disclose price in an organized market, their future transaction volumes have not developed sufficiently yet. However, future transaction volumes of non-ferrous metals like aluminum, tin etc. that are used as auxiliary raw materials in steel manufacturing have increased fast in organized markets and such style of future transactions have become important in steel manufacturing in terms of cost management. The London Metal Exchange, one of the leading future commodity markets of world, has an important place in management of price risk in steel manufacturing and consumption of derivative transaction contracts. In this study, causality relationship between the price series of non-ferrous metals used as raw materials in steel manufacturing is examined by using Toda and Yamamoto (1995) causality test procedure. Empirical results suggest that aluminum is Granger cause of the other non-ferrous metals. Keywords: causality relationship; LME; metal contracts; price risk. JEL Classifications: G13; L61